Urinary Dickkopf-3: a new biomarker for CKD progression and mortality. Issue 12 (19th June 2021) - Sánchez-Álamo, Beatriz; García-Iñigo, Francisco José; Shabaka, Amir; Acedo, Juan Manuel; Cases-Corona, Clara; Domínguez-Torres, Patricia; Diaz-Enamorado, Yunayka; Landaluce, Eugenia; Navarro-González, Juan F; Gorriz, José Luis; Martínez-Castelao, Alberto; Fernández-Juárez, Gema
Abstract: Background: Kidney fibrosis has been reported to be a prognostic factor in chronic kidney disease (CKD) progression. Previous studies have shown that the assessment of urinary Dickkopf-3 (uDKK3), a stress-induced tubular epithelial-derived profibrotic glycoprotein, might be a potential tubulointerstitial fibrosis biomarker and might identify patients at short-term risk of glomerular filtration rate loss. We aim to evaluate uDKK3 as a potential biomarker for progression of CKD in a cohort with various aetiologies of CKD and subsequently in an overt diabetic nephropathy cohort. Methods: We prospectively studied two independent cohorts comprising a total of 351 patients with Stages 2 and 3 CKD. Combined primary outcome consisted of a 50% increase in serum creatinine, end-stage kidney disease or death. The Progreser cohort included patients with heterogeneous aetiologies and the Pronedi cohort (101 patients) with overt diabetic nephropathy. The median follow-up time was 36 months [interquartile range (IQR) 30–39] and 36 (16–48), respectively. Results: At baseline, median uDKK3 was 2200 pg/mg (IQR 671–7617) in the Progreser cohort and 3042 pg/mg (IQR 661–9747) in the Pronedi cohort. There were no statistically significant differences in the uDKK3 ratio between both cohorts nor between CKD aetiologies. Baseline uDKK3 was significantly higher in patients who reached the primary outcome. In the Cox proportional hazards model, the highest levels of uDKK3 were found to be an independent factor for renal progression in the Progreser cohort hazard ratio [HR] 1.91 [95% confidence interval (CI) 1.04–3.52] and in the Pronedi cohort [HR 3.03 (95% CI 1.03–8.92)]. uDKK3 gradually increased in the following months, especially in patients with higher proteinuria. Treatment with renin–angiotensin–aldosterone system blockers did not modify uDKK3 after 4 or 12 months of treatment. Conclusions: uDKK3 identifies patients at high risk of CKD progression regardless of the cause of kidney injury. uDKK3 might serve as a useful biomarker for kidney disease progression and therefore could be used by clinicians to optimize staging for renal progression and monitor the response to potential treatments.